Exploring the determinants of performance of SMEs in South Punjab (Bahawalpur), Pakistan - Syed Usman Ali Gillani; Waseem Ahmad Khan; Muhammad Rizwan; Junaid Qureshi (Journal of Management Practices, Humanities and Social Sciences, 2021)
This research aims to find the information of factors that have significant effect and relationship with the performance of Small and Medium Enterprises (SMEs) located in South Punjab (Bahawalpur), Punjab, Pakistan. For this purpose, firstly, the qualitative and secondary data is searched in different ways. Data is collected in various ways. The data of SMEs is collected from the chamber of commerce and the Directory of Industrial establishment Punjab (District Bahawalpur). A total of 82 out of 100 questionnaires were filled out by the officials of different SMEs containing two sections. A Likert Scale questionnaire is adopted to collect specific data for the study and analysis through smart PLS. Industry environment, Exterior factors, Infrastructure, Monetary resources, Effective Entrepreneurship, and Accessibility of information have a relationship and affect SMEs' performance in Bahawalpur. This research has several limitations worthy of improvement and future study. First, it is based on respondents from a particular city. Second, it has a limited number of respondents. In future researcher use large area population for study.